(untitled) (Fiep Bulletin - online, 2014)
The present study intended to do a characterization of the functional aspects of Futsal professional players’ and compare them from different competitive levels and for tactical position carried out in the game. The sample was composed by 40 Futsal professional players, chosen intentionally, belonging to three teams that disputed the of Futsal championship of the state Rio Grande do Sul, organized for the Rio Grande do Sul Federation of Futsal, in the three available categories, series gold of the year 2001 (team of Ipiranga Futebol Clube), series silver year 2000 and series bronze year 1999 (teams of the Esporte Clube Itapagé). The potency maximum aerobics (Vo2max), the potency lactic anaerobic, the displacement agilities and mobility of the center of gravity, it forces abdominal and muscular potency of inferior members was analyzed through Analyses of Variance (ANOVA) among the teams and enter the game positions. The test "t" was used for data only contained in two groups. Concluding, a test of correlation of Pearson was accomplished among some you varied pertinent of investigation in this sense. The data evidenced that, when we compared athletes belonging to competitions of different technical levels it could be evidenced differences in the capacity neuromuscular of abdominal resistance, which was shown better conditioned the athletes of the silver series in relation to the bronze series. The displacement agility other capacity that she showed was also differentiated among the appraised teams. Finally, it was data significant statistical in the positive correlations for potency of inferior members with resistance lactic anaerobic and VO2max and negative correlations among displacement agility with resistance lactic anaerobic and with VO2max.